Sistem Informasi Pengolahan Data Kepangkatan Pegawai Negeri Sipil Pada Pengadilan Agama Kotabumi - Nurbaiti Nurbaiti; Silvie Chintya Melinda; Riski Putri Ameliya (Institut Bakti Nusantara, 2020)
Along with the development of information technology has become the main choice in the formation of a powerful corporate information system, information technology has also become one of the aspects of the institution has advantages and become a strategy in dealing with this increasing problem. The need for fast and accurate information is needed by an agency. Information becomes an important part of any decision making to support performance so that the objectives of the agency can be achieved. Computers is one of the media to support the need for fast and accurate information so that what is needed by the agency, can be managed properly. Local government officials as one in the local government as well as Religious Courts and so on, in the data processing of civil servant officers less than once accurate information because it is still manual using Microsoft Word in which the system is in the data PNS rank still less the maximum of which is often the loss of data and frequent occurrence of errors when inputting data keper PNS.